Effect of high temperature on the performance of self-compacting mortars produced with calcined kaolin and metakaolin - Arslan, Furkan; Benli, Ahmet; Karatas, Mehmet (Elsevier Sci Ltd, 2020)
The effects of high temperature up to 900 degrees C on the mechanical characteristics of self-compacting mortars (SCMs) containing different proportions of calcined kaolin (CK) and metakaolin (MK) were investigated in this study. The percentages of CK and MK that replace cement in this work were 0%, 5%, 10%, 15% and 20% by weight. The mechanical performance was assessed from compressive strength and flexural strength on the specimens of 40x40x160 mm size exposed 3, 28 and 90 day- water curing at ambient temperature and on the 28 day-specimens at high temperature while the durability of 28 day-SCMs samples was assessed from porosity, water absorption, sorptivity and density tests on water cured specimens of 50x50x50 mm size. The fresh properties of mortars were researched by slump and V-funnel tests. The rheological properties of fresh mortars were investigated by conducting the viscosity test. The outcomes of the study reveal that workability of mixtures was decreased with increasing proportion of MK replacement. The results also revealed that at 28 and 90 days of curing ages, the specimens of SCMs with MK15 gained the highest strength of 65.40 MPa and 79.01 MPa for about 10.13% and 15.46% more than the control specimens at the respective ages. Results illustrated that while the temperature rises, the compressive strength reduction of CK blended SCMs samples decreases with increasing replacement ratio of CK. A remarkable reduction in the total water absorption and porosity values of MK blended SCMs samples was observed. The highest density values at all SCMs mixes were observed for MK5 blended samples about 8.44% increase. 15% replacement level of MK gives the lowest sorptivity values. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Self-Compacting Mortars; Elevated Temperature; Calcined Kaolin; Metakaolin; Mechanical Properties; Transport Properties